Analisis Nilai Moral dalam Novel Balada Gimpul Karya Langit Kresna Hariadi - Nana Sakinah; Kamiri Kamiri; Nori Anggraini (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
A literary work basically contains moral values conveyed by the author to teach all aspects of life with the aim of changing one's behavior to be better than before. Because many people in this era are very poor in civilized. Even though in living in society moral values are very necessary related to the reflection of every human being, unfortunately moral values in living in society are now very minimal in application. A novel by Langit Kresna Hariadi in the title Balada Gimpul printed II, there is a depiction of moral values in social life. Researchers feel that this is suitable to be used as research material in the form of analysis and make the moral values contained in it as research objects. This analysis is qualitative with content analysis as the method used. Reference books and the Balada Gimpul novel will become references for data sources in this study. In addition, there are also techniques used in data collection, namely the technique of documentation and records. This data collection technique uses three components, namely data reduction, data presentation and drawing conclusions. Researchers believe that in order for this research to be feasible, appropriate procedures need to be applied in research including data collection, data classification, and re-analyzing classified data. Based on the results of the research, the authors found several aspects and criteria of moral values and divided them into positive and negative moral values in the novel Balada Gimpul..Keywords: Moral Values; Ballad Gimpul novel; The Sky of Krishna Hariadi.